(untitled) (Diametros, 2010)
The essay deals with problems that emerge in new interpretations of Hume’s famous argument concerning induction. In modern Hume scholarship there is a growing tendency to view Hume’s argument not as reasoning concerning the evidential value of our inductions but rather as a kind of explanation of the cognitive process of making causal inferences. The essay describes the main tenets of two currently dominant interpretations (skeptical and explanatory). In addition to discussing both interpretations, the article engages in a discussion about the meaning of Hume’s argument by confronting the old skeptical reading of Hume with new interpretations. My contribution to the discussion consists of two arguments against the explanatory tradition of viewing Hume’s argument.